2019
DOI: 10.3390/md17060351
|View full text |Cite
|
Sign up to set email alerts
|

Tunicate Heparan Sulfate Enriched in 2-Sulfated β-Glucuronic Acid: Structure, Anticoagulant Activity, and Inhibitory Effect on the Binding of Human Colon Adenocarcinoma Cells to Immobilized P-Selectin

Abstract: Heparin or highly sulfated heparan sulfate (HS) has been described in different invertebrates. In ascidians (Chordata-Tunicata), these glycosaminoglycans occur in intracellular granules of oocyte accessory cells and circulating basophil-like cells, resembling mammalian mast cells and basophils, respectively. HS is also a component of the basement membrane of different ascidian organs. We have analyzed an HS isolated from the internal organs of the ascidian Phallusia nigra, using solution 1H/13C NMR spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Despite the intrinsic heterogeneity, the distinct disaccharide components of mammalian HSs are often arranged as repetitive building-blocks along their chains [26]. Previous two-dimensional (2D) NMR spectra assessments performed by our group have already demonstrated that PNH possesses increased proportions of disaccharides containing N-acetyl α-glucosamine and/or β-glucuronic acid (>50%), which is characteristic of HSs, but they are randomly arranged along their chains [21].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Despite the intrinsic heterogeneity, the distinct disaccharide components of mammalian HSs are often arranged as repetitive building-blocks along their chains [26]. Previous two-dimensional (2D) NMR spectra assessments performed by our group have already demonstrated that PNH possesses increased proportions of disaccharides containing N-acetyl α-glucosamine and/or β-glucuronic acid (>50%), which is characteristic of HSs, but they are randomly arranged along their chains [21].…”
Section: Discussionmentioning
confidence: 94%
“…Fractions containing each peak were pooled together, dialyzed against distilled water, lyophilized and stored at −20 • C for further utilization. PNH disaccharide composition was previously shown by NMR analysis [21].…”
Section: Isolation and Purification Of Pnhmentioning
confidence: 99%
See 3 more Smart Citations